Teaching Without the Face: The Influence of Online Teaching on Professors’ Sense of Relational Responsibility - Heringer, Rebeca; Piquemal, Nathalie (Alberta Journal of Educational Research, 2022)
Although distance education is not a new phenomenon, the unprecedented advent of the COVID-19 pandemic left educators across the country with no option but to deliver their courses in an online format. Many studies have demonstrated the influence of distance education on teachers’ practices and several studies correlate teachers’ interaction to students’ motivation, participation, satisfaction, and performance in distance education. There is, however, a paucity of research that analyzes the influence of students’ physical presence on a teacher’s sense of relational responsibility, especially at the university level and with distance education—let alone when teaching online is not an option. The purpose of this study was therefore to understand the ways in which the abrupt and involuntary shift from physical to distance education caused by the COVID-19 pandemic and the absence of students’ physical presence affected teacher-educators’ perceived sense of relational responsibility, as articulated by Levinas. Semi-structured interviews were conducted with 12 professors teaching in Faculties of Education across Canada. The main question driving this research was: in what ways does the physical absence of students influence professors’ perceived sense of relational responsibility? Findings are presented and discussed under three main themes: relationships, responsibility, and responsivity. Key words: Teacher responsibility, online education, higher education, relationality Bien que l'enseignement à distance ne soit pas un phénomène nouveau, l'avènement sans précédent de la pandémie du COVID-19 a laissé les éducateurs de tout le pays sans autre choix que de donner leurs cours dans un format en ligne. Alors que de nombreuses études ont démontré l'influence de l'enseignement à distance sur les pratiques des enseignants et que plusieurs études mettent en corrélation l'interaction des enseignants avec la motivation, la participation, la satisfaction et les performances des élèves dans l'enseignement à distance, il existe peu de recherches analysant l'influence de la présence physique des élèves sur le sens de la responsabilité relationnelle d'un enseignant, en particulier au niveau universitaire et avec l'enseignement à distance—et encore moins lorsque l'enseignement en ligne n'est pas une option. Le but de cette étude était donc de comprendre la manière dont le passage brusque et involontaire de l'éducation en personne à l'éducation à distance causé par la pandémie de COVID-19 et l'absence de présence physique des élèves ont affecté le sentiment perçu de responsabilité relationnelle des enseignants-formateurs, tel qu'articulé par Levinas. Des entrevues semi-structurées ont été menées avec 12 professeurs enseignant dans les facultés d'éducation du Canada. La principale question qui a motivé cette recherche était la suivante : de quelle manière l’absence physique des étudiants influence-t-elle le sentiment perçu par les professeurs de responsabilité relationnelle ? Les résultats sont présentés et discutés sous trois thèmes principaux : les relations, la responsabilité et la réactivité. Mot clés : Responsabilité des enseignants, enseignement en ligne, enseignement supérieur, relationnalité